Analisis Yuridis Wanprestasi dalam Akad Gadai Syariah dan Pertanggungjawaban Ahli Waris: Studi Kasus Putusan PA Tangerang No. 2070/Pdt.G/2024/PA.Tng - A.M. Fadli Dzil Jalal; Rahmat Rahmat; Sahman Z (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2025)
This study discusses breach of contract (wanprestasi) in Islamic pawn agreements (rahn) and the liability of heirs for the debts of the deceased, based on a case study of the Religious Court Decision of Tangerang No. 2070/Pdt.G/2024/PA.Tng. The primary focus is a juridical analysis of how the judge structured the resolution of default disputes in a rahn contract, particularly when the debtor (rahin) passes away before settling the debt. This research employs a normative juridical legal method with statutory, conceptual, and maqasid al-shariah approaches. The findings show that the judge harmoniously integrates principles of civil law and Islamic law by emphasizing that the deceased’s debts must first be settled from the estate before it can be distributed among the heirs. The heirs are not personally liable for any remaining debt beyond the value of the inherited estate. The ruling aligns with Article 833 of the Indonesian Civil Code, Article 175 paragraph (1) of the Compilation of Islamic Law, and the values of maqasid al-shariah, particularly the protection of wealth (ḥifẓ al-māl) and justice (‘adl). This research contributes to the development of Islamic economic law, especially in resolving defaults with comprehensive legal, moral, and social considerations. Thus, the decision reflects substantive justice and legal certainty for all parties.